Study on Culex Mosquitoes of Bhelukhel, Bode and Tathali of Bhaktapur District, Nepal - Shrestha, Monica; Gautam, Ishan; Gupta, Ranjana (Journal of Natural History Museum, 2015)
An entomological study was carried out in Bhelukhel, Bode and Tathali of Bhaktapur district to compare fluctuation in population size of Culex mosquitoes in relation to relative humidity and temperature. Mosquitoes were collected during July-December 2012 around the pig enclosures and cattle sheds by means of dark activated rechargeable CDC light trap. The study resulted 73.41% of Culex mosquitoes out of the total mosquitoes collected (884). Total eleven species of Culexmosquitoes were recorded namely Cx. tritaeniorhynchus, Cx. fuscocephala, Cx. gelidus, Cx. vishnui, Cx. pseudovishnui, Cx. bitaeniorhynchus, Cx. quinquefasciatus, Cx. edwardsi, Cx. hutchnsoni, Cx. whitei and Cx.whitmorei. Distribution of Culexspecies was abundant in July and August. Cx. quinquefasciatus, the principal vector of Lymphaticfilariasis (LF) was recorded to be the most dominant species in all the three sites. Cx. tritaeniorhynchus, the principal Japanese encephalitis (JE) vector was collected in higher number during August from Tathali and Bode site and during July from Bhelukhel site. Significant variation was not observed in abundance of Culex mosquito in three study sites in six different months. J. Nat. Hist. Mus. Vol. 28, 2014: 118-126